A novel hollow iron nanoparticle system loading PEG-Fe3O4 with C5a receptor antagonist for breast cancer treatment - Yang, Hong; Li, Guiqing; Zhang, Ji; Zhao, Jing; Zhao, Yunpei; Wu, Yufei; Sun, Zihan; Song, Shuangshuang; Zou, Ying; Zou, Zhihao; Han, Xiao; Deng, Boshao; et al. (Frontiers in Immunology, 2024)
Breast cancer is the most diagnosed malignancy and major cause of cancer death among women population in the worldwide. Ferroptosis is a recently discovered irondependent regulated cell death involved in tumor progression and therapeutic response.Moreover, increasing studies have implied that ferroptosis is a promising approach to eliminating cancer cells like developing iron nanoparticles as a therapeutic agent.However, resistance to ferroptosis is a vital distinctive hallmark of cancer. Therefore, further investigation of the mechanism of ferroptosis resistance to enhance its tumor sensitivity is essential for ferroptosis-target breast cancer therapy.Our results revealed that the activation of C5a/C5aR pathway can drive resistance to ferroptosis and reshaping breast cancer immune microenvironment. Accordingly, Loading PEG-Fe3O4 with C5aRA significantly improved the anti-tumor effect of PEG-Fe3O4 by inhibiting ferroptosis resistance and increasing macrophage polarization toward M1 phenotype. Our findings presented a novel cancer therapy strategy that combined cancer cell metal metabolism regulation and immunotherapy. The study also provided support for further evaluation of PEG-Fe3O4@C5aRA as a novel therapeutic strategy for breast cancer in clinical trials.